4-[2-(Chlorodiphenylstannyl)phenyl]-4-hydroxybutan-2-one - Adrian-Alexandru Someșan; Richard A. Varga (Molbank)
An aldol condensation reaction between [2-(O=CH)C6H4]SnPh2Cl and acetone gave [2-{CH3C(=O)CH2(OH)CH}C6H4]SnPh2Cl (1). The compound was characterized in a solution using multinuclear NMR spectroscopy and HR-MS spectrometry and in a solid state using IR spectroscopy and single-crystal X-ray diffraction. The molecular structure revealed the presence of both enantiomers in the crystal.